2019
DOI: 10.26552/com.c.2019.3.35-39
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Strength and Anisotropy of Dmls Manufactured Maraging Steel

Abstract: This paper deals with maraging steel, as a prospective material for the 3D printed lightened structural parts of transport means. Direct Metal Laser Sintering technology was tested for creation of a thin-wall structure with defined internal geometry. The referential samples prepared by the DMLS technology were examined under quasi-static and high strain rate loading using a servo-hydraulic testing machine at strain rates up to 1400 s-1. Microstructural analyses served for evaluation of structural homogeneity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…So, it can be expected to be best choice for high strength applications. Eva Schmidova et al [87] found that DMLS maraging steel contains fine micro structure when compared to forging or casting and which is responsible for high dynamic and static strength. It was found that aging heat-treatment reduced Plastic anisotropy levels to a greater extent, however, transverse strain anisotropy was likely to remain due to the AM alloy's fabrication history [88] .…”
Section: Characteristics Of Ni-based Super Alloysmentioning
confidence: 99%
“…So, it can be expected to be best choice for high strength applications. Eva Schmidova et al [87] found that DMLS maraging steel contains fine micro structure when compared to forging or casting and which is responsible for high dynamic and static strength. It was found that aging heat-treatment reduced Plastic anisotropy levels to a greater extent, however, transverse strain anisotropy was likely to remain due to the AM alloy's fabrication history [88] .…”
Section: Characteristics Of Ni-based Super Alloysmentioning
confidence: 99%
“…That means a precipitation hardening, which makes steel achieve enormous strength. But tested samples were only after the primary stage of production, that means without hardening to determine the effect of the used technology, including the natural surface relief (Schmidova et al, 2019). Only solution annealing heat treatment was applied: heating in a protective atmosphere to the austenitization temperature was applied -the endurance at this temperature was 1 hour, then followed by rapid cooling below 500 °C, followed by cooling on air.…”
Section: Maraging Steel Ms1mentioning
confidence: 99%
“…(Milewski, 2017) The initiation of the use of metal 3D printing in production requires considerable research into material properties, which may differ from commonly used materials. As an example may be a different microstructure of steel or anisotropy of mechanical properties in different directions of loading/testing, see (Schmidova et al, 2019). Also, subsequently when using internal structures designed to lighten the part while maintaining good functionality, we can get to the solution of unusual material testing tasks.…”
Section: Introductionmentioning
confidence: 99%